Traders’ Preference in Choosing Expedition Partner in Tanah Abang Market - Wahyu Teri Aripin; Sukmadi Sukmadi; Nuslih Jamiat (Jurnal Sekretaris dan Administrasi Bisnis, 2018)
Choosing expedition partner has been becoming a crucial issue for those who are running retail business in this digital era. Having the right partner in expedition to work with can be another competitive advantage for the company itself. In this era, almost every transaction would be done online, therefore the meeting between sellers and buyers is no longer necessary in some cases; but still the trust between them must be maintained. Choosing the right expedition is one of the ways to maintain that trust. The right expedition partner here will be defined as those expedition company who can guarantee to deliver product faster (on schedule), cheaper for the service price and also easy to be contacted. Tanah Abang itself is the biggest market in Jakarta. This place has been chosen as the object for the research because the sellers here are actively selling product both offline and online. Descriptive approach has been used for the research methodology. Data are generated from questionnaire and interview. All data that have been gathered will show the number of seller or trader who is actively purchase expedition services in a week. Besides that, it is cleared seen which and why such expedition company leading the market.